New user? Sign up

Existing user? Sign in

I want to solve this problem be without computer assisted solution.

Note by Chung Kevin 2 years, 6 months ago

Sort by:

Note first that \(a = 512 = 2^{9}, b = 675 = 3^{3}5^{2}\) and \(c = 720 = 2^{4}3^{2}5,\) and thus \(2c^{2} = 3ab.\)

Next, note that

\(a^{3} + b^{3} + c^{3} = a^{3} + b^{3} - c^{3} + 2c^{2}c = a^{3} + b^{3} - c^{3} + 3abc = (a + b - c)(a^{2} + b^{2} + c^{2} - ab + ac + bc).\)

Thus \(a + b - c = 512 + 675 - 720 = 467\) divides the given expression, i.e., the given expression is composite.

Log in to reply

Nice observation with \( 2c^3 = 3ab \)!

512^3-512+675^3-675+720^3-720+(512+675+720) by fermats little theoram it is divisible by 3

Hm, can you explain in detail? I'm pretty sure that the number is not a multiple of 3.

The problem here is the fact that hcf is one. So, I feel that fermats little theorem must be used

Problem Loading...

Note Loading...

Set Loading...

## Comments

Sort by:

TopNewestNote first that \(a = 512 = 2^{9}, b = 675 = 3^{3}5^{2}\) and \(c = 720 = 2^{4}3^{2}5,\) and thus \(2c^{2} = 3ab.\)

Next, note that

\(a^{3} + b^{3} + c^{3} = a^{3} + b^{3} - c^{3} + 2c^{2}c = a^{3} + b^{3} - c^{3} + 3abc = (a + b - c)(a^{2} + b^{2} + c^{2} - ab + ac + bc).\)

Thus \(a + b - c = 512 + 675 - 720 = 467\) divides the given expression, i.e., the given expression is composite.

Log in to reply

Nice observation with \( 2c^3 = 3ab \)!

Log in to reply

512^3-512+675^3-675+720^3-720+(512+675+720) by fermats little theoram it is divisible by 3

Log in to reply

Hm, can you explain in detail? I'm pretty sure that the number is not a multiple of 3.

Log in to reply

The problem here is the fact that hcf is one. So, I feel that fermats little theorem must be used

Log in to reply